Economic Growth and Accessibility Improvement in Lahomi District - Feby Milanie (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Economic growth in a region is strongly influenced by the quality of accessibility that supports the movement of goods, people, and economic activities. This study aims to analyze the relationship between improved accessibility and economic growth in Lahomi District, an area experiencing rapid development but still facing transportation and infrastructure limitations. Using a descriptive qualitative approach supported by secondary data, this research examines the influence of road conditions, transportation availability, and infrastructure development on economic performance in the district. The findings indicate that improvements in accessibility—such as upgraded road networks, increased transportation connectivity, and better public service infrastructure—have contributed significantly to enhancing local economic activities, reducing logistical barriers, and supporting community mobility. However, several challenges remain, including limited transportation facilities and uneven infrastructure development across villages. Strengthening accessibility is therefore essential to achieving sustainable economic growth in Lahomi District. The study concludes that continuous infrastructure improvement and strategic regional planning are necessary to optimize economic potential and foster inclusive development.